(untitled) (Cadernos de Sociomuseologia, 2019)
The Worshop ICAMT Lisbon 2018 links Architecture with Museology specifically focusing on museum techniques, community museums, and energy and sustainability. It is intended for students and professionals in architecture, engineering, museology, plastic arts, curatorship, design and related areas. It will analyze methodological, conceptual and technical issues related to the role of architecture in the implementation of museological projects, focusing on contemporary museographic techniques, the role of community museums in 21st century society and the need to use renewable energies, contributing to the sustainability of museums. The Workshop aims to bring to the discussion these three thematic axes contributing to enrich and consolidate the good practices of museums professionals Thematic axes of the workshop 1. Museographic techniques - role of architecture: - In times of financial crisis and low budgets in museums, how architecture can produce museographic solutions that are both low-cost and effective in communication; - Intelligent use of information technology in museographic techniques. 2. Role of community museums in the 21st century: - Community Museums in the digital society of the 21st century; - Community museums and the current society of mass migrations; - The responsibility, innovation and creativity of architecture in small museums; 3. Renewable energies and museum sustainability: -To make the renewable energies available, what are the best solutions for sustainability in its various aspects, applied to museums; - Inclusion of building automation (domotics) in museums. Scientific Board Jean Hilgersom Alessandra Labate Rosso Aida Rechena Judite Primo Nana Meparishvili Manuel Furtado Mendes Mário Moutinho